Utility of movement disorder society-unified Parkinson's disease rating scale for evaluating effect of subthalamic nucleus deep brain stimulation - Yamamoto, Tatsuya; Yamanaka, Yoshitaka; Hirano, Shigeki; Higuchi, Yoshinori; Kuwabara, Satoshi (Frontiers in Neurology, 2023)
Background The Movement Disorders Society (MDS)-Unified Parkinson's Disease Rating Scale (UPDRS) is increasingly used to assess motor dysfunction before and after subthalamic nucleus deep brain stimulation (STN-DBS). Objectives We, therefore, investigated whether the MDS-UPDRS can detect longitudinal changes in motor function after STN-DBS in the same way as UPDRS. Methods We examined 21 patients with Parkinson's disease (PD) (mean age 59.2 ± 10.6 years, mean disease duration 12.0 ± 3.0 years) who underwent STN-DBS and whose motor functions were assessed by the UPDRS and MDS-UPDRS before, 3 months after, and 1 year after STN-DBS. We then evaluated the consistency between the scores of Parts II and III of the UPDRS and MDS-UPDRS during the off phase using Lin's concordance coefficient (LCC) and a Bland-Altman plot. Results The scores of Parts II and III of both the UPDRS and MDS-UPDRS were significantly decreased 3 months and 1 year after STN-DBS during the off phase. Scores of the UPDRS and MDS-UPDRS showed significant positive correlations before and after STN-DBS. We calculated estimated MDS-UPDRS scores from the UPDRS scores using a regression line and calculated the LCC between the MDS-UPDRS and the estimated MDS-UPDRS scores. The LCC value was 0.59–0.91, which suggests a relatively high consistency between the UPDRS and MDS-UPDRS. The Bland-Altman plot showed that differences between both scores were basically within ±1.96 standard deviations of the difference. Conclusion The present preliminary study indicated that the utility of the MDS-UPDRS in evaluating motor function before and after STN-DBS demonstrates its potential equivalency to the UPDRS.